A critical humanist intervention: agency, structure and values - Arukia izabel (Global Writing Academica Researching and Publishing, 2023)
The main aim of the article is to suggest what and how a contemporary and revised version of humanism, inflected with critical realism and Marxism, can contribute to sociology. I mainly focus on two areas in which sociology is often lacking today: theorizing the relationship between structure and agency, and deciding what to do with moral evaluations in sociological analyses. I submit that the solution for both lies in trying finally to transcend the traditionally hostile and mutually exclusive paradigms of